Impact of Magnification Views on the Characterization of Microcalcifications in Digital Mammography - Fallenberg, E. M.; Dimitrijevic, L.; Diekmann, F.; Diekmann, S.; Kettritz, U.; Poellinger, A.; Bick, U.; Winzer, K. J.; Engelken, F.; Renz, D. M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To evaluate the additional benefit of true geometric (air-gap) magnification views for the characterization of microcalcifications in digital mammography.Materials and Methods: After ethical approval, we retrospectively reviewed patient records to identify 100 patients with suspicious microcalcifications (35 malignant, 65 benign) who had a standard digital mammography and an additional digital magnification view in the same projection within three months. All images were obtained using an amorphous silicon-based full-field digital system (Senographe 2000 D, GE Healthcare, Chalfont St. Giles, UK). Images were independently analyzed by six board-certified radiologists. The probability of malignancy was estimated using first standard contact mammography alone (MG) and then mammography in combination with the magnification view (MG+MAG) using a modified Breast Imaging Reporting and Data System (BI-RADS) classification system and a percentage scale. Results were compared using receiver operating characteristic (ROC) analysis. In addition, readers assessed the subjective visibility of the calcifications.Results: For all six readers combined, the area under the curve (AUC) was 0.664 ± 0.052 for MG and 0.813 ± 0.042 for MG + MAG, resulting in a statistically significant improvement of 0.148 ± 0.120. Each reader had a higher AUC for MG + MAG than MG, with the improvement being statistically significant in four of the six readers. In 76.34 % of the cases, MG + MAG resulted in better visibility of calcifications compared with mammography alone. In 33 % slightly more and in 39 % significantly more calcifications were found.Conclusion: Even in digital mammography with the option of using electronic magnification (zoom) at the viewing workstation, true geometric (air-gap) magnification views remain important for the visibility and correct classification of microcalcifications and for the assessment of their extent.Citation Format:• Fallenberg EM, Dimitrijevic L, Diekmann F et al. Impact of Magnification Views on the Characterization of Microcalcifications in Digital Mammography. Fortschr Röntgenstr 2014; 186: 274 – 280
Keywords: breast; breast radiography; screening; mammography; microcalcifications